Implementasi Kebijakan Keterbukaan Informasi Publik (KIP) Berbasis Grand Digital Pemerintah Kota Pasuruan - Lutfiyah, Lutfiyah; Muchsin, Slamet; Kurniati, Rini Rahayu (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The openness of public bodies in providing information to the public is a responsibility that must be carried out in accordance with the mandate of the KIP Law. The objectives of this research are to (1) Analyze the stages of the Pasuruan City Government Information Communication and Statistics Department in implementing the policy of UU KIP No. 14 of 2008. (2) Describe what obstacles arise in implementing the policy of UU KIP No. 14 of 2008 ( 3) Understand the success in implementing the KIP Law No. 14 of 2008 policy. This research uses a qualitative research approach, namely research that requires a deep understanding of the interactions between analyzes or concepts in depth regarding the relationships of concepts that are studied empirically. The results of this research are (1) the stages of the Pasuruan City Government Information Communication and Statistics Service in implementing the policy of the KIP Law No. 14 of 2008. (a) Identification of Strategic Issues in Efforts to Implement KIP. (b) Follow-up Plan to Encourage KIP Implementation Efforts. (c) Results of Policy/Program Implementation in Encouraging KIP Implementation Efforts. (2) Obstacles that arise in implementing the KIP Law policy. (3) Success in implementing the policies of UU KIP No. 14 of 2008.